2006
DOI: 10.1111/j.1365-2133.2006.07474.x
|View full text |Cite
|
Sign up to set email alerts
|

Bleomycin and the skin

Abstract: Bleomycin is frequently used as a chemotherapeutic agent to treat various kinds of malignancy. However, the cytotoxic effects of bleomycin cause a number of adverse responses, in particular in the lung and the skin. Bleomycin is used by dermatologists as a treatment for various skin cancers, recalcitrant warts, keloid and hypertrophic scars. This article discusses the use of bleomycin for various skin disorders, as well as the risk factors and cutaneous side-effects resulting from its use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
115
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(116 citation statements)
references
References 99 publications
(175 reference statements)
0
115
0
1
Order By: Relevance
“…The recommended dosage starts at 0.1 ml (1.5 IU/ml) and can go up to a maximum dose of 6 ml in order to prevent adverse effects which are usually cutaneous and less common pulmonary. 31,32 For patients with old scars that do not respond to intralesional steroid, the recommended treatment is between 2 and 6 sessions per month. Bleomycin usage is still uncommon in the clinical practice.…”
Section: Bleomycinmentioning
confidence: 99%
“…The recommended dosage starts at 0.1 ml (1.5 IU/ml) and can go up to a maximum dose of 6 ml in order to prevent adverse effects which are usually cutaneous and less common pulmonary. 31,32 For patients with old scars that do not respond to intralesional steroid, the recommended treatment is between 2 and 6 sessions per month. Bleomycin usage is still uncommon in the clinical practice.…”
Section: Bleomycinmentioning
confidence: 99%
“…[1][2][3][4] The striking bleomycin-induced skin hyperpigmentation, as in our case, needs to be expected, and oncologists should discuss this adverse event with their patients before treatment. Primary care physicians should also be aware of this reaction because these patients may present for routine examinations.…”
Section: Resultsmentioning
confidence: 99%
“…2 It is widely used to treat a variety of malignancies and warts, and it is used in chemical pleurodesis. 2 Bleomycinrelated dermatologic toxicities include alopecia, skin ulceration (predominantly plantar-palmar), eczematous changes, erythematous bullae, sclerodermoid lesions, nail-bed changes, Raynaud phenomenon, painful inflammatory nodules on the fingers, warty hyperkeratotic plaques on the knees and elbows, digital gangrene, blisters, infiltrated violaceous plaques, and flagellate dermatitis. 1,2,5 Other side effects include pneumonitis that may lead to lung fibrosis, which is an absolute indication to stop bleomycin therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,33 The pathogenesis of scleroderma involves a complex interplay between vascular damage, inflammation, and fibrosis; however, the detailed mechanisms remain to be determined. 2,25,44 It has been suggested that factors released from inflammatory cells in the early stages lead to the formation of myofibroblasts capable of producing collagens, resulting in fibrosis. 15,17,21,27,45 In particular, macrophages are thought to act as important cells for the onset of scleroderma.…”
mentioning
confidence: 99%